Epidemiology of Influenza from 2007 to 2008 in Naha Area, Okinawa Prefecture: Surveillance of Rapid Antigen Test Results - Yara, Satomi; Yamane, Nobuhisa; Naka, Masamitsu; Higa, Futoshi; Tateyama, Masao; Haranaga, Syusaku; Fujita, Jiro; Koide, Michio (Japanese Journal of Infectious Diseases, 2009)
The incidence of influenza in the Naha city area in the southernmost part of Japan was surveyed in 2007 and 2008. Patients who had influenza-like symptoms and visited one of four general hospitals in Naha City, Okinawa, Japan were included in this study. The nasal or throat swab samples were applied to the rapid test for detecting influenza A and B virus antigens. The positive rate of influenza A and/or B virus antigen was 26.2% (8,480/32,380). Most cases (82.9%) were influenza A. In 2007, influenza A cases were detected during the entire year, and an epidemic peak was also noted in July, while no outbreak occurred in the summer of 2008. The surveillance of the rapid influenza virus antigen test seemed to provide reliable epidemiological data. This finding warrants further study in this region, including study of the influences of climate and socio-behavior patterns of the residents in the region on influenza epidemics.